(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crimes and criminal justice policies are one of the reasons for the continuing increase in the number of PDLs or "PERSONS DEPRIVED OF LIBERTY," resulting in the overcrowding of jails in the Philippines. Overcrowding has a huge impact on PDL’s physical and mental health. It may lead to a lot of negative effects such as increased prevalence of communicable and chronic diseases, lack of proper hygiene, increase in violence, and mental health problems. According to the congestion rate summary statistics of BJMP, 638% is the average congestion rate in NCR as of September 30, 2022. There are a lot of overcrowded city jails in NCR, and, as a matter of fact, Quezon City Jail is one of the most crowded jails in the region. More than 4,000 PDL are incarcerated in this city Jail. The study revealed that the respondents were experiencing difficulty sleeping caused by overcrowding and heat, insufficient hygiene, eating tasteless food, being prone to committing suicide, polluted areas, lack of ventilation, and transmission of disease due to Insufficient space. There were many ways that could be used to resolve the overcrowding, such as facility expansion and environmental improvement, Speeding up the probation application process, and Providing a budget to build another prison for PDL in the neighboring province of our city. For further enhancement of the facilities of jail and to decrease the high number of PDL, The government should offer a job for those people who do not achieve a high standard of education or are not college graduates to avoid discrimination because poverty is one of the reasons why others are able to act against our law to survive on a daily basis, that way the population of criminals who are caught every day will be reduced.